2007
DOI: 10.1128/jb.00466-07
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Site Occupancy by stx 2 Bacteriophages Depends on the Locus Availability of the Host Strain Chromosome

Abstract: Shiga toxin-producing Escherichia coli (STEC) is an emergent pathogen characterized by the expression of Shiga toxins, which are encoded in the genomes of lambdoid phages. These phages are infectious for other members of the Enterobacteriaceae and establish lysogeny when they integrate into the host chromosome. Five insertion sites, used mainly by these prophages, have been described to date. In the present study, the insertion of stx 2 prophages in these sites was analyzed in 168 STEC strains isolated from ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 40 publications
7
79
0
4
Order By: Relevance
“…The presence of cdt in phages, although not always inducible, has been reported (11) and is supported by the P2 sequences (12) or lambdoid phage sequences (15) found in the flanking regions of cdt in several bacterial isolates. In this study, a new Cdt-V phage, named ⌽AA91, was used to lysogenize S. sonnei strain 866, since this strain gave good results in studies with Cdt phages (14) and also had previously shown the capacity to generate lysogens of temperate Stx bacteriophages (21,36). No lysogens of ⌽AA91 were obtained with any of the other laboratory strains assayed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of cdt in phages, although not always inducible, has been reported (11) and is supported by the P2 sequences (12) or lambdoid phage sequences (15) found in the flanking regions of cdt in several bacterial isolates. In this study, a new Cdt-V phage, named ⌽AA91, was used to lysogenize S. sonnei strain 866, since this strain gave good results in studies with Cdt phages (14) and also had previously shown the capacity to generate lysogens of temperate Stx bacteriophages (21,36). No lysogens of ⌽AA91 were obtained with any of the other laboratory strains assayed.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered members of the lambdoid family, since they share a common genome arrangement that conserves the relative positions of the genes with similar activities and associated regulatory signals (7). Although Shiga toxin-encoding bacteriophages are a heterogeneous group in terms of morphology and their genetic organization (24,33,46,54), the location of stx genes is conserved, being found next to the lytic genes and downstream of the Q antiterminator (36). Therefore, Shiga toxin production is basically linked to the induction or progression of the phage lytic cycle after activation of the SOS response in the bacterial host.…”
mentioning
confidence: 99%
“…The toxin is released through cell lysis (55). Following the lytic burst, Stx phages act as vectors in the stx horizontal transmission to other members of the family Enterobacteriaceae (1,2,19,33,44,46,51).…”
mentioning
confidence: 99%
“…The insertion sites of the phages used in this study (wrbA for all phages except A9, which inserts in yecE) (20) were confirmed to be the same in the WT and in DH5␣⌬baeSR.…”
Section: Role Of Envelope Stress Responses In the Generation Of Stx2 mentioning
confidence: 98%
“…DH5␣⌬baeSR with a pGEM vector without an insert was used as a negative control. The Stx2 phages used in this study differed genetically from each other, and some also had different insertion sites (14,20). Phage lysates containing 10 7 PFU/ml were used for at least three to five independent assays.…”
Section: Role Of Envelope Stress Responses In the Generation Of Stx2 mentioning
confidence: 99%